Regulatory Review on Policy of Special Allocation Fund for Road Sector in 2015-2019 - Naufal Azaki; Achmad Lutfi (Universitas Teuku Umar, 2023)
Regulation is one of the critical instruments for implementing a policy. State regulations function at least to provide legal certainty, guidelines/instructions, frameworks, and limitations of program/policy implementation. The special allocation fund is an intergovernmental transfer for financing road infrastructure under the local government authority and aligned with national priorities. This study aims to analyze the regulatory framework that governs the implementation of this capital grant for the road sector by taking the 2015-2019 timeframe. The research is qualitative and uses a normative juridical method through a statute approach using primary material in the form of laws and regulations related to the 2015-2019 capital grants for the road sector. The results showed several regulatory incompleteness, discrepancies in content both horizontally and vertically, and weaknesses in legal blanket for monitoring and evaluation. This study recommends strengthening the harmonization of regulations to ensure no inconsistencies or contradictions. Furthermore, the study also emphasizes the importance of conducting regulatory review considering that the long-term development planning (RPJPN) of 2025-2045 is being drafted so that such precedents of disharmonization do not occur anymore.